2014
DOI: 10.1074/jbc.m114.566893
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled Receptor 30 (GPR30) Forms a Plasma Membrane Complex with Membrane-associated Guanylate Kinases (MAGUKs) and Protein Kinase A-anchoring Protein 5 (AKAP5) That Constitutively Inhibits cAMP Production

Abstract: Background: GPR30 plays important roles in cardiometabolic regulation and cancer. Results: GPR30 forms a complex with a MAGUK and AKAP5 that constitutively inhibits cAMP production independently of G i/o and retains receptors in the plasma membrane. Conclusion:The GPR30-MAGUK-AKAP5 complex mediates receptor signaling. Significance: These results present a new mechanism by which a receptor inhibits cAMP production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
76
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 46 publications
12
76
0
1
Order By: Relevance
“…Leeb-Lundberg and colleagues similarly have reported that GPER is constitutively endocytosed from the plasma membrane of HEK-293 and MDCK cells [Sanden et al, 2011]. The PDZ domain encoded at the C-terminus of the GPER cytoplasmic tail has been implicated in the retention of GPER at the plasma membrane in HEK-293 and MDCK cells [Broselid et al, 2014;Tran et al, 2015] and its recruitment to dendritic spines in hippocampal neurons [Akama et al, 2013]. These studies provide evidence that the PDZ domain in GPER forms receptor complexes that may influence receptor dimerization, signaling and/or endocytosis.…”
Section: Gper: Immunolocalization Subcellular Sites Of Receptor Actionmentioning
confidence: 80%
See 2 more Smart Citations
“…Leeb-Lundberg and colleagues similarly have reported that GPER is constitutively endocytosed from the plasma membrane of HEK-293 and MDCK cells [Sanden et al, 2011]. The PDZ domain encoded at the C-terminus of the GPER cytoplasmic tail has been implicated in the retention of GPER at the plasma membrane in HEK-293 and MDCK cells [Broselid et al, 2014;Tran et al, 2015] and its recruitment to dendritic spines in hippocampal neurons [Akama et al, 2013]. These studies provide evidence that the PDZ domain in GPER forms receptor complexes that may influence receptor dimerization, signaling and/or endocytosis.…”
Section: Gper: Immunolocalization Subcellular Sites Of Receptor Actionmentioning
confidence: 80%
“…These studies provide evidence that the PDZ domain in GPER forms receptor complexes that may influence receptor dimerization, signaling and/or endocytosis. These studies demonstrate an interaction with the postsynaptic density (PSD)-95 scaffolding protein [Akama et al, 2013;Tran et al, 2015], membrane-associated guanylate kinases (MAGUKS) and protein-kinase A-anchoring protein 5 (AKAP5) [Broselid et al, 2014] and plasma membrane Ca2+-ATPase 4b (PMAC) [Tran et al, 2015]. Nonvisual arrestins-2/-3 do not appear to be involved in GPER endocytosis as they do not colocalize with GPER in early endosomes and arrestin-2 dominant negative mutants lacking either clathrin-or β-adaptin-interaction sites do not block GPER internalization [Cheng et al, 2011].…”
Section: Gper: Immunolocalization Subcellular Sites Of Receptor Actionmentioning
confidence: 97%
See 1 more Smart Citation
“…In PSD-95 null mice, serotonin 2C receptor (5-HT 2C R)-mediated cfos induction is impaired (Abbas et al, 2009). Despite significant sequence homology, PSD-95 appears to have opposing roles in regulating its trafficking and signaling pathways of 5-HT 2A R and (Akama et al, 2013;Broselid et al, 2014). PSD-95 has also been reported to positively regulate dopamine 1 receptor (D 1 R) endocytosis and inhibit D 1 R-mediated cAMP formation (Zhang et al, 2007b).…”
Section: Gpcr-interacting Psd-95 Family Pdz Domain-mentioning
confidence: 99%
“…Recently another GPCR, GPR30, was added to the list of AKAP-interacting GPCRs. GPR30 was shown to form a PDZ motif-dependent plasma membrane complex with a membrane-associated guanylate kinase (likely SAP97 or PSD-95) and AKAP5, which led to the constitutive attenuation of cAMP production and retained the receptor at the plasma membrane (148).…”
Section: Pdz Proteinsmentioning
confidence: 99%